Sex and Brain: The Role of Sex Chromosomes and Hormones in Brain Development and Parkinson’s Disease - Francesca Terrin; Annachiara Tesoriere; Nicoletta Plotegher; Luisa Dalla Valle (Cells, 2023)
Sex hormones and genes on the sex chromosomes are not only key factors in the regulation of sexual differentiation and reproduction but they are also deeply involved in brain homeostasis. Their action is crucial for the development of the brain, which presents different characteristics depending on the sex of individuals. The role of these players in the brain is fundamental in the maintenance of brain function during adulthood as well, thus being important also with respect to age-related neurodegenerative diseases. In this review, we explore the role of biological sex in the development of the brain and analyze its impact on the predisposition toward and the progression of neurodegenerative diseases. In particular, we focus on Parkinson’s disease, a neurodegenerative disorder that has a higher incidence in the male population. We report how sex hormones and genes encoded by the sex chromosomes could protect from the disease or alternatively predispose toward its development. We finally underline the importance of considering sex when studying brain physiology and pathology in cellular and animal models in order to better understand disease etiology and develop novel tailored therapeutic strategies.